Reverse arthroplasty for osteoarthritis and rotator cuff deficiency after previous surgery for recurrent anterior shoulder instability - Raiss, Patric; Zeifang, Felix; Loew, Markus (International orthopaedics, 2014)
Purpose: Osteoarthritis in combination with rotator cuff deficiency following previous shoulder stabilisation surgery and after failed surgical treatment for chronic anterior shoulder dislocation is a challenging condition. The aim of this study was to analyse the results of reverse shoulder arthroplasty in such patients. Methods: Thirteen patients with a median follow-up of 3.5 (range two to eight) years and a median age of 70 (range 48–82) years were included. In all shoulders a tear of at least one rotator cuff tendon in combination with osteoarthritis was present at the time of arthroplasty. The Constant score, shoulder flexion and external and internal rotation with the elbow at the side were documented pre-operatively and at the final follow-up. Pre-operative, immediate post-operative and final follow-up radiographs were analysed. All complications and revisions were documented. Results: Twelve patients were either satisfied or very satisfied with the procedure. The median Constant score increased from 26 points pre-operatively to 67 points at the final follow-up (p = 0.001). The median shoulder flexion increased significantly from 70° to 130° and internal rotation from two to four points (p = 0.002). External rotation did not change significantly (p = 0.55). Glenoid notching was present in five cases and was graded as mild in three cases and moderate in two. One complication occurred leading to revision surgery. Conclusions: Reverse arthroplasty leads to high satisfaction rates for patients with osteoarthritis and rotator cuff deficiency who had undergone previous shoulder stabilisation procedures. The improvements in clinical outcome as well as the radiographic results seem to be comparable with those of other studies reporting on the outcome of reverse shoulder arthroplasty for other conditions.